Fossil seaward-dipping reflector sequences preserved in southeastern Australia: a 600 Ma volcanic passive margin in eastern Gondwanaland - Direen, NG; Crawford, AJ (2003)
Evidence for a c. 600 Ma rifted passive margin in eastern Australia exists in the form of multiple belts of mafic volcanic rocks preserved along the western margin of the Tasman Fold Belt System, and giving rise to elongate magnetic anomalies. Outcrop, drillhole and geophysical evidence points to piles of lavas, volcaniclastic and intrusive rocks up to 6 km thick, extending for strike lengths of hundreds of kilometres in individual segments. The distinctive, unifying characteristics of these piles are apparent common formation ages (600-580 Ma), presence of early more landward transitional alkaline basalts, and more seaward abundant rift tholeiites, with high-temperature picrites and olivine-rich basalts at most localities. Despite later structural reorganization, these belts have close geochemical, geometric and lithological affinities with Mesozoic seaward-dipping reflector sequences along the North Atlantic, and northwestern Australian volcanic passive margins, and strongly imply the formation of a volcanic passive margin in eastern Gondwanaland at the close of the Neoproterozoic. Recognition of this event has implications for the position of an implied earlier rifted margin related to the break-up of Rodinia around 780 Ma. A rifting event at 600 Ma in eastern Gondwanaland helps explain both the lack of evidence for volcanism from Rodinia break-up, and a widespread 600 Ma population of inherited zircons within rocks of the Lachlan Orogen, which developed outboard of the passive margin in earliest Palaeozoic time.